Defect Engineering on Carbon-Based Catalysts for Electrocatalytic CO2 Reduction - Xue, Dongping; Xia, Huicong; Yan, Wenfu; Zhang, Jianan; Mu, Shichun (Nano-Micro Letters, 2020)
Electrocatalytic carbon dioxide (CO2) reduction (ECR) has become one of the main methods to close the broken carbon cycle and temporarily store renewable energy, but there are still some problems such as poor stability, low activity, and selectivity. While the most promising strategy to improve ECR activity is to develop electrocatalysts with low cost, high activity, and long-term stability. Recently, defective carbon-based nanomaterials have attracted extensive attention due to the unbalanced electron distribution and electronic structural distortion caused by the defects on the carbon materials. Here, the present review mainly summarizes the latest research progress of the construction of the diverse types of defects (intrinsic carbon defects, heteroatom doping defects, metal atomic sites, and edges detects) for carbon materials in ECR, and unveil the structure–activity relationship and its catalytic mechanism. The current challenges and opportunities faced by high-performance carbon materials in ECR are discussed, as well as possible future solutions. It can be believed that this review can provide some inspiration for the future of development of high-performance ECR catalysts. Highlights: 1 The main construction methods of carbon-based nanomaterials (CBN) with different defects are systematically introduced. 2 The structure–activity relationship of defective carbon-based catalysts in electrocatalytic carbon dioxide reduction (ECR) reaction is mainly reviewed. 3 Challenges and opportunities of high-performance defective CBN in ECR and the possible solutions in the future are discussed.